Tidal current in Kuala Terengganu coastal waters. - Saadon, M.N.; Yaacob, Rosnan
The aim of this study is to investigate how important are tides and/or wind to the water movements in the Kuala Terengganu coastal waters. Water current is known to be the main transporter of sediment in the sea which can result in coastal erosion. Information on water movements will hopefully add up to the vast information that have been gathered so far in order to understand the cause of the extensive erosion along the Kuala Terengganu coast. The study was conducted from the month of February to June 1990. A foru-day trip was scheduled per month on board R.V.UNIPERTAMA I. The study area was along the coast of Kuala Terengganu. Four stations were chosen where two stations were about 0.5 naut.mile and the other two were about 4.0 naut. mile and the other two were about 4.0 naut. miles from the shore. Three drogues with depths of 1m,3m,and 5m were used to track the water movement. The drogues were released at 0800 hrs and were allowed to drift for over 10 daylight hours. Their positions were taken at every one-hour interval. Tidal data were obtained from Tide Tables and Wind Data from the Meteorogical Station. The study clearly shows that tide is the main parameter that shapes the current pattern in the study area. This current is generally referred to as the tidal current. Wind on the other hand,has the least effect on the water movement in the study area.